Pengaruh Team Assisted Individualization Terhadap Keterampilan Passing Dalam Pembelajaran Basket Siswa Kelas Viii Smpn 1 Karawang Barat - Syamhari, Wijaya; Susianti, Evi; Dermawan, Dikdik Fauzi (Peneliti.net, 2026)
The purpose of this study is to determine the extent of the influence of the Team Assisted Individualization (TAI) learning model on passing skills in basketball learning among eighth-grade students at SMPN 1 Karawang Barat. This study employed a quantitative approach using a quasi-experimental research method. The research was conducted at SMPN 1 Karawang Barat. The population consisted of 480 eighth-grade students. The sampling technique used in this study was cluster random sampling, applying the Slovin formula. Based on this method, a sample of 83 students was selected. The research design used was a pre-experimental design in the form of a one-group pretest-posttest design. The research instrument utilized a skill-based test focused on the basic passing techniques in basketball. The results of the study showed a significant improvement in the average scores before and after treatment: the mean pretest score for chest pass increased from 60.67 to a posttest mean of 81.23; for bounce pass, from 57.55 to 82.82; and for overhead pass, from 51.75 to 69.22. Furthermore, the hypothesis testing using the Paired Sample T-Test revealed a significance value (2-tailed) of 0.000, which is less than 0.05. This indicates a statistically significant difference between the pretest and posttest scores. It can be concluded that the Team Assisted Individualization (TAI) learning model has a positive and significant impact on the improvement of passing skills in basketball among eighth-grade students at SMPN 1 Karawang Barat